Effect of Tilt-adjustable Mouse Pad on the Forearm Muscle Activity and Upper Limb Discomfort During a Computer Mouse Task - Hamid Salmani Nodooshan; Hadi Daneshmandi; Alireza Choobineh; Farzaneh Yazdani; Mohsen Razeghi; Taymaz Shahnazar Nezhad Khales (Shiraz University of Medical Sciences, 2023)
Background: Musculoskeletal disorders in the upper extremities are common among computer users. This study aimed to assess the effect of mouse pad angle on the forearm muscles activity and upper limb discomfort.Methods: This is an experimental research design. The mouse pad was set at 0, 10, 20, and 30 degrees of forearm supination. Ten subjects performed an identical text editing task with mouse in each pad position. Electrical activity of the selected forearm muscles was recorded with surface electrodes. 10-point rating scales were used for assessing perceived discomfort.Results: Extensor Carpi Radialis had the lowest mean of Electromyography (EMG) values in the 0° slanted pad (5.94), and the highest values were associated with Pronator Quadratus in 0-degree slanted pad (22.29). The highest and the lowest mean (SD) of the users' upper limb discomfort were 3.70 (1.63) and 1.90 (1.28) in 30° and 10° slanted pads, respectively.Conclusion: Using slanted mouse pads could be a helpful and practical tool for office workers to keep more neutral wrist/hand positions.